The Slang Word Used by Students of English Language Education, Ganesha University Education on Instagram Story - Ni Putu Eva Agustini Sari (Pusat Studi Bahasa dan Publikasi Ilmiah, 2021)
Previous research stated that many millennials are comfortable in applying the use of slang in their daily communication. However, there is difficulty among the elderly about the use of slang that makes them face obstacles in knowing the meaning behind the slang used. Therefore, this research has an objective to investigate what kind of slang words used by them on their Instagram account. This research is kind of descriptive qualitative research using observation method, that wants to examine the slang words used by 15 students of English Language Education, Ganesha University of Education on Instagram especially from Instagram story feature. The findings indicate that it exists four types of slang used by Students of English Language Education on Instagram story, namely fresh and creative with total number of slangs is 12; imitative is six; for acronym, the total number of slangs used is three; and clipping with total number of slangs is 10. It indicates that mostly the slang used is type of fresh and creative and the most rarely used in flippant.